Terrestrial: Toward an ecological emergence in music - Jauhiainen, Ilpo; Cobussen, Marcel; Assis, Paulo de (Ghent Orpheus Instituut, 2028)
The research examines the potentiality of emergence and environmental intelligence as a compositional and performative tool. It focuses on a de/reterritorialization process that – to borrow from Deleuzian terminology – is becoming-environment of music and becoming-music of an environment. The key questions are: how could environmental intelligence – an integration of environmental data and knowledge with artificial intelligence (AI) – be applied as a compositional system for generative music? And how could environmentally sensitive and responsive music operate in the age of accelerated environmental change and ever-ubiquitous intelligent technology?Drawing from Assemblage Theory, Hyperobjects, New Materialism and Posthumanism, the research seeks to formulate a new 21st century musical practice and aesthetic as that of a constructive agency between environment, music, technology and philosophy; to posit an idea of composer/performer as a facilitator – philosopher, gardener, catalyst – between contemporary society, science and sonic arts. It aims to develop an ecosystemic approach to 'AI in music' where AI operates as one of the agents in a greater ecology of human and more-than-human intelligences. The focus is on generative (self-organising and -evolving) musical practices that cover electroacoustic and contemporary classical music, new global musical styles as well as the emerging possibilities and combinations of music and sound art.Alongside written theoretical work and a series of compositions and performances, the practice-based research consists of developing an AI application (‘Terrestrial’) that will act as an intelligent algorithmic tool between the composer/performer and a given environment (e.g. an ecosystem, hyperobject, network or assemblage) – actual or virtual.
2028-09-30
FRIS
1
Keywords: MetamusicX:Transdisciplinary Encounters in and Beyond Music